Exploring Students’ Perception Toward Wattpad in Students’ Reading Skill: A Qualitative Study - Pradita Anti Nurmahmiati (Faculty of Education, 2025)
This research aims to explore students' perceptions of using Wattpad to read and improve their English reading skills. The background of this research is based on students' lack of interest and motivation in reading, especially when faced with intensive reading that is often rigid and uninteresting. Wattpad, as a reading application that is widely used, especially among teenagers, offers a more flexible, fun, and interesting reading experience and can affect students' motivation and comprehension in reading English texts. This research used a qualitative descriptive approach with data collected through interviews with three high school students who had used Wattpad to read English stories. Thematic analysis was used to identify patterns and perceptions from their responses.
reapload repository maret 2026 Rudi H
Keywords: Exploring Students’; Perception Toward; Wattpad in Students’; Reading Skill